Long-term consequences of sexually transmitted infections on men's sexual function: A systematic review. Issue 3 (3rd July 2021) - Henkel, Ralf
ABSTRACT: Objective : To systematically review the available literature on the long-term effects of sexually transmitted diseases (STIs) on male reproductive functions. Methods: A PubMed search was conducted on 3 January 2021, and as a result, 952 articles were retrieved. Exclusion of irrelevant articles resulted in 36 articles, dating from 1998 to 2020, which were analysed. Results: Only 52.8% of these articles described original research, while the rest were reviews. The majority (26) of the articles dealt with bacterial infections, of which 20 described Chlamydia trachomatis . There were 11 articles that described research on viruses, with five on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The analysis of the articles showed further that not much new knowledge on the long-term effects on male reproductive functions has been added. The existing knowledge that ascending infections can cause epididymo-orchitis, prostatitis or urethritis was confirmed. Due to epithelial inflammatory responses these infections can result in scarring with resulting infertility due to obstruction. These effects were described for Chlamydia trachomatis, Neisseria gonorrhoeae, Mycoplasma genitalium or Treponema pallidum, as well as for the Zika and SARS-CoV-2 viruses. Even trichomoniasis can lead to long-term compromised male fertility if not treated. Conclusion: In conclusion, problem awareness needs to be raised and more research on this important topic needs to be conducted.